2021
DOI: 10.1002/cpt.2375
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Plasma Coproporphyrin‐I Concentration as Biomarker of OATP1B Activity in Patients With Rheumatoid Arthritis

Abstract: Organic anion transporting polypeptides (OATPs) 1B are drug transporters mainly expressed in the sinusoidal membrane. In previous reports, genetic factor, 3‐carboxy‐4‐methyl‐5‐propyl‐2‐furanpropanoic acid (CMPF), which is one of the uremic toxins, inflammatory cytokines such as tumor necrosis factor‐α (TNF‐α) and interleukin‐6 (IL‐6) decreased OATP1B1 activity in vitro, but in vivo effects of these factors have not been elucidated. Plasma coproporphyrin‐I (CP‐I) is spotlighted as a highly accurate endogenous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 32 publications
1
15
2
Order By: Relevance
“…However, the concentrations of exposure were very high: 10 ng/mL of IL‐6 and 100 ng/mL of TNF‐α, which are rarely observed in human plasma. Further, in our previous study in patients with RA, there was no correlation between plasma CP‐I concentration and plasma IL‐6 or TNF‐α concentration 17 . Multiple regression analysis in the present study found that the contribution of CRP concentration to plasma CP‐I concentration was less than that of blood CyA concentration.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…However, the concentrations of exposure were very high: 10 ng/mL of IL‐6 and 100 ng/mL of TNF‐α, which are rarely observed in human plasma. Further, in our previous study in patients with RA, there was no correlation between plasma CP‐I concentration and plasma IL‐6 or TNF‐α concentration 17 . Multiple regression analysis in the present study found that the contribution of CRP concentration to plasma CP‐I concentration was less than that of blood CyA concentration.…”
Section: Discussioncontrasting
confidence: 63%
“…CMPF is one of the uraemic toxins that accumulate in patients with CKD. Our previous studies in healthy volunteers and patients with CKD 16 or RA 17 uncovered a positive correlation between plasma CP‐I and CMPF concentrations. Additionally, multivariate analysis identified plasma CMPF concentration and OATP1B polymorphism as significant factors affecting plasma CP‐I concentration 17 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The endogenous substrates of OATP1B, such as coproporphyrin I (CP‐I), is considered as functional biomarkers to detect changes of OATP1B activity by OATP1B inhibitor drugs, when the administration of probe drugs is not practical 8,9 . CP‐I has also been used to investigate genetic variations in OATP1B1*15 10–12 and the effect of disease conditions on OATP1B activities 13,14 . Significant effect of OATP1B1 genotypes on the plasma CP‐I concentrations supports major contribution of OATP1B1 to the hepatic uptake of CP‐I.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 CP‐I has also been used to investigate genetic variations in OATP1B1*15 10 , 11 , 12 and the effect of disease conditions on OATP1B activities. 13 , 14 Significant effect of OATP1B1 genotypes on the plasma CP‐I concentrations supports major contribution of OATP1B1 to the hepatic uptake of CP‐I. Likewise, after administration of an inhibitor of OATP1B1/1B3, the plasma concentration of CP‐I displayed a transient increase, and the magnitude of change in the maximum plasma concentrations (C max ) and the area under the plasma concentration time curve (AUC) depend on the magnitude of OATP1B inhibition during the study.…”
Section: Introductionmentioning
confidence: 99%